2024
DOI: 10.3390/catal14020105
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Buffer Nature on Immobilized Lipase Stability Depend on Enzyme Support Loading

Pedro Abellanas-Perez,
Diego Carballares,
Javier Rocha-Martin
et al.

Abstract: The lipases from Thermomyces lanuginosus (TLL) and Candida antarctica (B) (CALB) were immobilized on octyl-agarose beads at 1 mg/g (a loading under the capacity of the support) and by overloading the support with the enzymes. These biocatalysts were compared in their stabilities in 10 mM of sodium phosphate, HEPES, and Tris-HCl at pH 7. Lowly loaded CALB was more stable than highly loaded CALB preparation, while with TLL this effect was smaller. Phosphate was very negative for the stability of the CALB biocata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 125 publications
0
1
0
Order By: Relevance
“…In the literature [40], it has been pointed out that for studies involving the use of an immobilized enzyme performed in different buffers, the nature of the buffer significantly influences the stability of the lipase immobilized via interfacial activation and, also that phosphate usually generates negative results in biocatalyst stability, including the CALB. Moreover, it is indicated that the enzyme loading (potentially by intermolecular interaction) and the nature of the buffer, apart from the effect on the enzyme stability, also impact enzyme catalytic activity or specificity [43].…”
Section: Effect Of Buffer Phmentioning
confidence: 99%
“…In the literature [40], it has been pointed out that for studies involving the use of an immobilized enzyme performed in different buffers, the nature of the buffer significantly influences the stability of the lipase immobilized via interfacial activation and, also that phosphate usually generates negative results in biocatalyst stability, including the CALB. Moreover, it is indicated that the enzyme loading (potentially by intermolecular interaction) and the nature of the buffer, apart from the effect on the enzyme stability, also impact enzyme catalytic activity or specificity [43].…”
Section: Effect Of Buffer Phmentioning
confidence: 99%